2020
DOI: 10.1002/ehf2.12859
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of animal and plant foods and risk of left ventricular diastolic dysfunction: the Bogalusa Heart Study

Abstract: Aims Left ventricular diastolic dysfunction (LVDD) is an early heart failure with preserved ejection fraction (HFpEF) phenotype that is reversible. Identifying dietary predictors associated with LVDD in diverse populations may help broadly improve HFpEF primary prevention. Methods and results This longitudinal analysis included 456 individuals of the Bogalusa Heart Study (27% Black, 63% women, baseline age = 36.1 ± 4.4 years). Diet was measured at baseline through food frequency questionnaires. LVDD was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…To the best of our knowledge, only two studies have evaluated the impact of plant-based diets on heart functionality. In a prospective study conducted on 456 individuals, with a median followup of 12.9 years, a lower risk of left ventricular diastolic dysfunction (LVDD), evaluated with echocardiography, was observed among people with a higher legume and vegetable intake [68]. Notably, in this study, even with low statistical significance, total and animal proteins were associated with higher risks of LVDD in women but not in men.…”
Section: Plant-based Dietscontrasting
confidence: 51%
See 1 more Smart Citation
“…To the best of our knowledge, only two studies have evaluated the impact of plant-based diets on heart functionality. In a prospective study conducted on 456 individuals, with a median followup of 12.9 years, a lower risk of left ventricular diastolic dysfunction (LVDD), evaluated with echocardiography, was observed among people with a higher legume and vegetable intake [68]. Notably, in this study, even with low statistical significance, total and animal proteins were associated with higher risks of LVDD in women but not in men.…”
Section: Plant-based Dietscontrasting
confidence: 51%
“…In contrast, fresh vegetable consumption conferred higher protective effects in men than in women. No differences were observed between different ethnicities [68]. The other study compared vegan and omnivorous amateur athletes (22 vegan athletes and 30 omnivorous) and showed that vegan athletes had a lower left ventricular mass and relative wall thickness but also a higher GLS [69].…”
Section: Plant-based Dietsmentioning
confidence: 94%
“…A high dietary fibre intake has also been shown to affect the incidence of hypertension, another risk factor associated with CVDs [ 105 ]. Several studies suggested that the consumption of SDF provides a safe way to reduce blood pressure [ 106 , 107 , 108 ]. In a Mediterranean cohort study, an inverse relation was found between cereal fibre intake and the risk of hypertension [ 109 ].…”
Section: Dietary Fibre From Whole Grains and Health Implicationsmentioning
confidence: 99%
“…The most consumed foods in the green food group were bananas, beans, tomatoes, mangoes, oranges, passion fruit, apples, potatoes, pineapples and watermelon. Razavi et al [ 44 ] observed that the intake of diets rich in foods of animal origin and low in vegetables is associated with an increased risk for left ventricular diastolic dysfunction, an alteration associated with mortality.…”
Section: Discussionmentioning
confidence: 99%